Development and application of the Weibull distribution-based vehicle survivorship models for a metropolis of a developing country - Rith, Monorom (Animo Repository, 2020)
Vehicle survival rate models have been extensively built in developed countries and China in view of the availability of vehicle scrappage data, but many developing countries do not have those data. This paper intends to develop Weibull distribution-based models of vehicle survivorship for Metro Manila, Philippines, without using the vehicle scrappage data. The proposed computation procedure can capture the dynamics of average vehicle lifespan. Light-duty passenger vehicles are classified into two main categories: car (sedan, hatchback) and utility vehicle (SUV, van, minivan, pickup, wagon, Jeepney). The results highlighted that the average lifespan of the car decreased from 23.23 years in 2007 to 15.22 years in 2016, whereas the average lifespan of the UV was constant and equal to 14.18 years. Also, the developed models were applied to project the vehicle stocks, scrapped vehicles, and vehicle sales based on two designed scenarios: historical trend and limitation of the vehicle stocks. © 2020, Prince of Songkla University. All rights reserved.